2017
DOI: 10.2298/gensr1703935b
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of farmer-preferred cowpea (Vigna unguiculata L. Walp) landraces in Turkey and evaluation of their relationships based on agromorphological traits

Abstract: 2017): Genetic diversity of farmerpreferred cowpea (Vigna unguiculata L. walp) landraces in Turkey and evaluation of their relationships based on agromorphological traits. Vol 49, No.3, Cowpea (Vigna unguiculata L. Walp) is one of the important vegetable, grain, and fodder legume species grown in the tropics and subtropics. Cowpea is grown on small farms, and locally adapted landraces or populations are cultivated, and genetic improvements are limited by the lack of knowledge of genetic diversity of the indig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
1
4
0
2
Order By: Relevance
“…Our study certain the presence of a high phenotypic diversity among cowpea genotypes studied in the current investigation exhibiting a good start for plant development programs to release hybrid and new varieties. Our results are in line with those observed by Hedge and Mishra (2009), Stoilova and Pereira (2013), Mafakheri et al (2017), Lazaridiet al (2017, Bozokalfa et al (2017) and El-Nahrawy (2018) who reported high phenotypic diversity among cowpea genotypes. Generally, Data analysis were considered for the polymorphic and reproducible excreted by the eleven ISSR primers, and ten SRAP primer pairs.…”
Section: Phenotypic Distances Between Parentssupporting
confidence: 93%
“…Our study certain the presence of a high phenotypic diversity among cowpea genotypes studied in the current investigation exhibiting a good start for plant development programs to release hybrid and new varieties. Our results are in line with those observed by Hedge and Mishra (2009), Stoilova and Pereira (2013), Mafakheri et al (2017), Lazaridiet al (2017, Bozokalfa et al (2017) and El-Nahrawy (2018) who reported high phenotypic diversity among cowpea genotypes. Generally, Data analysis were considered for the polymorphic and reproducible excreted by the eleven ISSR primers, and ten SRAP primer pairs.…”
Section: Phenotypic Distances Between Parentssupporting
confidence: 93%
“…According to Singh et al. (2007) and Bozokalfa et al. (2017) , many small-scale farmers deliberately favour shortened planting dates over longer durations in order to prevent complete crop failure.…”
Section: Discussionmentioning
confidence: 99%
“…Börülce yetiştiriciliği süresince meydana gelen ve tüketici tercihleri doğrultusunda şekillenen ve temelinde agronomik özelliklere yön veren karakterler bakımından varyabilite diğer araştırıcılar tarafından vurgulanmıştır (Benner-Lartey and Ofori, 1999;Othman et al, 2006;Cobbinah et al, 2011;Gbaguidi et al, 2015). Genotipler arasında görülen agronomik ve morfolojik özellikleri içeren fenotipik varyasyonların temelinin genetik varyasyonlar olduğu bildirilirken varyasyonların genetik açıdan farklı populasyonlardan kaynaklandığı işaret edilmektedir (Bozokalfa et al, 2017).…”
Section: Araştirma Bulgulari Ve Tartişmaunclassified